Immigrant languages and the veneto dialect in the linguistic repertoires of secondary school pupils of immigrant origin in the veneto region - Fincati, Verónica (My University)
Este estudio investiga los repertorios lingüísticos de los niños de origen inmigrante en la región de Véneto, que incluyen el italiano, el dialecto véneto y las lenguas inmigrantes. Se distribuyeron cuestionarios sociolingüísticos en tres escuelas secundarias de la región de Véneto, para recopilar información sobre la elección y el mantenimiento del idioma. Un total de 149 alumnos cumplimentaron el cuestionario, representando a 23 nacionalidades. Más de la mitad eran marroquíes, rumanos, albaneses, moldavos y chinos, los cinco principales grupos de inmigrantes en la región. Los resultados muestran diferentes grados de mantenimiento y uso de idiomas inmigrantes entre diferentes nacionalidades. También revelan el uso del dialecto véneto en la comunicación por parte de niños de segunda generación con compañeros, compañeros de clase, dentro del dominio familiar y en comunicación con italianos nativos (vecinos y en tiendas).

This study investigates the linguistic repertoires of children of immigrant origin in the Veneto region, which include Italian, the Veneto dialect and immigrant languages. Sociolinguistic questionnaires were distributed in three secondary schools in the Veneto region, to collect information on language choice and maintenance. A total of 149 pupils filled in the questionnaire, representing 23 nationalities. More than half were Moroccan, Romanian, Albanian, Moldovan and Chinese, the five main immigrant groups in the region. The results show different degrees of both maintenance and use of immigrant languages among different nationalities. They also reveal the use of the Veneto dialect in communication by second generation children with peers, classmates, within the family domain and in communication with native Italians (neighbours and in shops).
Artículos en revistas